2021
DOI: 10.52922/ti78030
|View full text |Cite
|
Sign up to set email alerts
|

Early-career offending trajectories among outlaw motorcycle gang members

Abstract: This study examines the criminal histories of outlaw motorcycle gang (OMCG) members during adolescence and early adulthood to determine whether the profile of young members has changed over time. The recorded offence histories of three cohorts of members—those born between 1979 and 1983, 1984 and 1988, and 1989 and 1993—were compared. Seventy-eight percent of OMCG members across all three cohorts had at least one recorded offence between the ages of 12 and 24. The majority of offenders did not desist but conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The findings indicate that criminal involvement is an important risk factor for selection into OMCGs: individuals who have been suspected of committing a crime at least once are 8.5 times more likely to be registered as OMCG members than are individuals who have not been suspected of committing a crime (Chapter 2). These findings align with previous research which finds that a large part of the OMCG population is already criminally involved in their pre-membership years (Blokland et al, 2017b;Klement, 2016b;Voce et al, 2021).…”
Section: Selectionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings indicate that criminal involvement is an important risk factor for selection into OMCGs: individuals who have been suspected of committing a crime at least once are 8.5 times more likely to be registered as OMCG members than are individuals who have not been suspected of committing a crime (Chapter 2). These findings align with previous research which finds that a large part of the OMCG population is already criminally involved in their pre-membership years (Blokland et al, 2017b;Klement, 2016b;Voce et al, 2021).…”
Section: Selectionsupporting
confidence: 91%
“…This study, however, also indicated large differences in the offending patterns of various Australian OMCG chapters: over a five-year period 5% of the chapters was responsible for 33% of the total registered crime and 48% of the total drug supply offenses (Morgan et al, 2020). Furthermore, Voce et al (2021) showed that younger OMCG members, already prior to the age of 25,…”
Section: Empirical Research Into the Criminal Activities And Criminal...mentioning
confidence: 65%
See 1 more Smart Citation
“…All offences were classified into five offence categories (see Table 1) consistent with previous research on OMCGs (e.g., Barker 2015;Voce et al 2021). This categorisation facilitated analyses of collaboration networks by crime types.…”
Section: Coding and Analysismentioning
confidence: 99%
“…OMCG membership has also been found to increase the risk of involvement in crime (Klement 2016a(Klement , b, 2019 and offending among OMCG members has been shown to be more prevalent, more frequent and more serious compared with motorcycle owners who are not members of OMCGs (Blokland et al 2019). Critically, there is evidence of an increasing prevalence of young members with recorded histories of crime, and especially violent crime (Lauchs 2017;Voce et al 2021;Van Dueren et al 2020). It has been posited that at least part of the attraction of these younger men to OMCGs is the potential for profitable criminal endeavours, including criminal collaboration in such crimes with established OMCG networks Boland et al 2021).…”
Section: Outlaw Motorcycle Gangsmentioning
confidence: 99%